1979
DOI: 10.1007/bf00257569
|View full text |Cite
|
Sign up to set email alerts
|

201Tl in the scintigraphic evaluation of the ?cold? thyroid areas

Abstract: 201Tl-chloride, which has a metabolic behaviour similar to that of potassium and cesium, has been used in 68 patients for the evaluation of thyroid nodules previously recognized as "cold" on 131I or 99mTc scans. All patients were re-examined with gamma-camera and/or sequential scintigraphic recordings during 60 min after i.v. administration of thallium. In some cases, simultaneous imaging and integral digital plot with 131I or 99mTc and 201Tl were performed. In all 12 malignant nodules, 201 Tl has showed a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

1981
1981
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
9
1
Order By: Relevance
“…The magnitude and specificity of 201T1 thyroid uptake was used for thyroid imaging. While the resulting scintigrams yielded an image similar to that obtained after injection of 99rnTc pertechnetate, neither their quality, nor their diagnostic contribution or correlation with various aspects of thyroid pathology justifies the preferential utiliza¬ tion of 201T1 (Palermo et al 1979;Fukuchi et al 1977Fukuchi et al , 1978. 201TI thyroid imaging has been found, however, to be useful in the differentiation of benign vs. malignant tumours, when combined with "mTc or 131I scans (Haradaetal.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The magnitude and specificity of 201T1 thyroid uptake was used for thyroid imaging. While the resulting scintigrams yielded an image similar to that obtained after injection of 99rnTc pertechnetate, neither their quality, nor their diagnostic contribution or correlation with various aspects of thyroid pathology justifies the preferential utiliza¬ tion of 201T1 (Palermo et al 1979;Fukuchi et al 1977Fukuchi et al , 1978. 201TI thyroid imaging has been found, however, to be useful in the differentiation of benign vs. malignant tumours, when combined with "mTc or 131I scans (Haradaetal.…”
Section: Discussionmentioning
confidence: 86%
“…201Thallium (201T1) is widely used for the visuali¬ zation of the normal and injured myocardium (Botvinick et al 1978;Dunn et al 1978). As an incidental finding it has been repeatedly observed that the thyroid was also visualized (Atkins et al 1977;Palermo et al 1979), suggesting a high deposition of 201T1 in the gland. This deposition has also been studied in experimental animals (Oster et al 1978).…”
mentioning
confidence: 90%
“…As previously reported in part (8), this technique of investigation now consists of: i.v. injection of 15-20 jiCi/kg of 2 0 1 Tl-chloride; sequential scintigrams using a gamma-camera (Searle-LFOV, HRC or pinhole collimators) on-line with with a data processing unit (Cine 230 Intertechnique); histo-mode recording 20s frames for the first 20-30 min and zoomdisplayed pictures; eventual simultaneous recording with double tracer ( 2( "T1 + " m Tc-500 (iCi) to pinpoint topographically any equivocal areas (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…summarizes the results in 120 consecutive patients examined according to the procedure and the interpretative criteria described; they were reevaluated in comparison with only qualitative diag-noses expressed in a larger non-selected group of 181 patients in which the former are included. The data of these patients were partly described in earlier reports(7,8).…”
mentioning
confidence: 90%
“…In the diagnosis of nodular goiter, many authors have reported the accumulation of this radionuclide in thyroid cancers and their lymphnode metastasis. [1][2][3][4][5][6][7] Meanwhile, since a significant fraction of adenomas or other benign conditions also appear positive in the scintigram, a single radiothallium image could not be a satisfactory test to use in estimating the Received February 4, 1991, revision accepted April 3, 1991. For reprints contact: Takashi Misaki, Department of Radiology, Kyoto City Hospital, Mibuhigashitakada, Nakagyoku, Kyoto 604, JAPAN. histological nature of a given struma nodosa.…”
Section: Introductionmentioning
confidence: 99%